Acetabular Bone Defect in Total Hip Arthroplasty for Crowe II or III Developmental Dysplasia of the Hip: A Finite Element Study. (25th August 2020) - Du, Yinqiao; Fu, Jun; Sun, Jingyang; Zhang, Guoqiang; Chen, Jiying; Ni, Ming; Zhou, Yonggang
Abstract : Background . The purpose of this study was to establish the finite element analysis (FEA) model of acetabular bone defect in Crowe type II or III developmental dysplasia of the hip (DDH), which could evaluate the stability of the acetabular cup with different types of bone defects, different diameters of femoral ceramic heads, and the use of screws and analyze the stress distribution of screws. Methods . The FEA model was based on the CT scan of a female patient without any acetabular bone defect. The model of acetabular bone defect in total hip arthroplasty for Crowe II or III DDH was made by the increasing superolateral bone defect area of the acetabular cup. Point A was located in the most medial part of the acetabular bone defect. A 52 mm PINNACLE cup with POROCOAT Porous coating was implanted, and two screws (the lengths were 25 mm and 40 mm) were implanted to fix the acetabular cup. The stability of the acetabular cup and the von Mises stress of point A and screws were analyzed by a single-legged stance loading applied in 1948 N (normal working). The different diameters of the femoral ceramic head (28 mm, 32 mm, and 36 mm) were also analyzed. Results . The von Mises stress of point A was gradually increased with the increasing uncoverage values. When the uncoverage values exceeded 24.5%, the von Mises stress of point A without screws increased significantly, leading to instability of the cup. Screws could effectively reduce the von Mises stress of point A with uncoverage values of more than 24.5%. However, the peak von Mises stress in the screws with the uncoverage values that exceeded 24.5% was considerably increased. The diameter of the femoral ceramic head had no significant effect on the von Mises stress and the stability of the acetabular cup. Conclusions . We recommend that uncoverage values of less than 24.5% with or without screw is safe for patients with Crowe II or III DDH.